Preparation and electrochemical properties of La1.5Pr0.5NiO4 and La1.5Pr0.5Ni0.9Cu0.1O4 cathode materials for intermediate-temperature solid oxide fuel cells. (May 2019) - Zhao, Chen; Zhou, Qingjun; Zhang, Ting; Qu, Liangwu; Yang, Xin; Wei, Tong
Graphical abstract: Highlights: LPN and LPNC cathodes offer good phase stability long-term phase stability at high temperatures. LPN and LPNC cathodes have thermal expansion coefficients similar to Ce0.8 Sm0.2 O1.9 electrolyte. Doping Cu in the Ni-site of the La1.5 Pr0.5 NiO4 improves electrochemical performances. offers good performance and phase stability. Abstract: Ruddlesden-Popper phases La1.5 Pr0.5 NiO4 (LPN) and La1.5 Pr0.5 Ni0.9 Cu0.1 O4 (LPNC) are synthesized by a modified complexing sol-gel process as cathode for intermediate temperature solid oxide fuel cells (IT-SOFCs). The X-ray powder diffraction characterization confirms the formation of pure single-phase of cathodes and the favorable chemical compatibility with the Sm0.2 Ce0.8 O1.9 (SDC) electrolyte. The thermal expansion coefficients (TECs) of the LPN and LPNC are 15.0 × 10 −6  K −1 and 14.5 × 10 −6  K −1, respectively. The electrical conductivities are 61 and 72 S. cm −1 for LPN and LPNC at 400 °C, respectively. The minimum polarization resistance (RP ) obtained on SDC electrolyte is 0.047 Ω cm 2 at 800 °C for LPNC cathode. The peak power density is 567 mW cm −2 for LPNC at 800 °C while 504 mW cm −2 for LPN in the same conditions. All the studies involved in this work show potential use of the LPNC cathode for IT-SOFCs.